PERAN IJMA’ SEBAGAI SUMBER HUKUM DALAM USHUL FIQIH - Muhammad Faqih Choiruddin; Arbi Nazhief Fauzan; Ilhamiyatul Hidayah; Reza Fandana (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Ijma’, one of the sources of Islamic law in the study of ushul fiqh, plays an important role in establishing sharia law, especially in cases where the Qur'an and Hadith do not provide a direct explanation of the issue. This article also discusses the position of ijma’ as the third source of law after the Qur'an and Hadith, as well as its importance to keep pace with the changes that have occurred in the lives of Muslims throughout history. In this article, a qualitative descriptive approach will be used to explain the different types of ‘ijma’, the requirements needed for it to be valid, and examples that can be applied in the context of rulings. Ijma’ not only demonstrates the intellectual agreement of the mujtahids but also shows the richness and flexibility of Islamic methods that respond to the challenges of the times while maintaining the basic values of the religion. This study aims to explain the position of ijma’ as a source of Islamic law after the Qur'an and Hadith, and to explain its forms, conditions, and relationship with meeting the legal needs of Muslims at various times. Since ijma’ is an important tool for maintaining the continuity and relevance of Islamic law in various social, cultural, and historical contexts, understanding ijma’ well is essential for building a flexible Islamic legal framework that remains grounded in the integrity of Islamic teachings.